Mighty Mount Kilimanjaro - Stilton, Geronimo (New York Broadway, 2024)
Rat-munching rattlesnakes! I can't believe it. I just let my super-sporty friend Bruce Hyena convince me to go on another one of his extreme adventures. You know me, I just can't say no to a friend! This time, we're going to be climbing to the top of the famous Mount Kilimanjaro in Africa. Moldy mozzarella! I'm in no shape for a montain climb. How will I ever make it to the top?Ch
Keywords: fiction